Use of Sealants in Permanent Molars by Brazilian Dentist: A Comparative Study of Public versus Private - Larissa Yumi Ito; Leticia Maíra Wambier; Ana Cláudia Rodrigues Chibinski; Manoelito Ferreira Silva Junior; Denise Stadler Wambier (Association of Support to Oral Health Research (APESB), 2024)
Objective: To compare the use of sealants in permanent molars between public and private dentists in Brazil. Material and Methods: This was a cross-sectional and analytical web survey study. The convenience sample consisted of dentists in Brazil who answered a pre-tested online form released via social media between July and October 2021. Descriptive analysis was performed using absolute and relative frequencies (%) and associations using the Chi-square test (p<0.05). Results: Brazilian professionals participated in the study (n=2,244). Comparing the professionals from the public service with those from the private service, the former had a higher positive perception of the use of sealants as a preventive (92.4% vs. 81.1%, p<0.001) and therapeutic procedure (90.7% vs. 82.4%, p=0.001), higher percentage of non-invasive (91.7% vs. 83.8%, p<0.001) and invasive (22.8% vs. 12.0%, p< 0.001) techniques. Professionals from the private service reported more frequently that they did not use sealants than those from the public service (14.0% vs. 4.8%, p<0.001). Resin sealant (97.7% vs. 94.9%, p=0.015) and Flow resin (62.0% vs. 54.3%, p=0.013) were the most used by professionals in the private service. The use of glass ionomer cement was not associated with the type of service (75.1% vs. 77.2%, p=0.172), nor was the use of adhesives (0.6% vs. 1.4%, p=0.195) or resin with Giomer technology (1.9% vs. 2.2%, p=0.856) (p>0.05). Conclusion: The percentage of use of sealants among dentists in Brazil is high, especially among professionals in the public service, and the most used materials were resinous sealants and glass ionomer cement.